Global Health diplomacy for noncommunicable diseases prevention and control: a systematic review - Mahnaz Afshari; Ahmad Ahmadi Teymourlouy; Mohsen Asadi-Lari; Mohammadreza Maleki (BMC, 2020)
Abstract Introduction The prevention and control of noncommunicable diseases (NCDs) are one of the main challenges of healthcare systems around the world. In addition to the technical level, it requires political negotiations and solutions, such as global health diplomacy (GHD), which involves the participation of a wide range of actors and stakeholders and innovative international health partnerships. This review aimed to draw lessons for strengthening linkages with a wide range of actors and stakeholders from the GHD literature for NCDs, and how policymakers and political leaders can effectively use international health partnerships to beat NCDs. Methods This research was a systematic review of the literature on GHD for NCDs. All relevant articles published in English were identified by searching PubMed, Web of Science, Scopus, and Embase databases, Google and Google Scholar search engines, and the reference lists of identified articles as well as a number of special journals. 30 articles that met the inclusion criteria were analyzed using content analysis in MAXQDA 10. The Global Health Diplomacy Pyramid and Blouin and Dubé's (2010) analytical framework for examining negotiations were used to classify the data. Findings 30 articles have been published on GHD for NCDs. Five key themes, i.e. the specific problem requiring global collective action, key actors, their interests in the problem, potential negotiation process, and potential scenarios for collective action and 46 sub-themes were identified. Moreover, given the importance of collaboration on NCDs in the international arena, actors were categorized into three groups based on the GHD Pyramid: (1) core diplomacy, (2) multi-stakeholder diplomacy, and (3) informal diplomacy. Conclusion Development and adoption of a global policy to tackle the rise in NCDs in developed and developing countries require policymakers and political leaders that participate in GHD. Successful developments in global health policy depend on the performance of and respectful relationships among the stakeholders, and global health diplomats need to understand the complexities of the institutional structures and functional relationships of the international institutions involved in health.